Functional Outcome (Short Term) of Modular Cementless Bipolar HemiArthroplasty (Hydroxyapatite-Coated Stem) for Fracture Neck of Femur in the Elderly - Navin K. Shukla; Lata Keshkar; Jayanta Mukherjee; Ratnesh Kumar; Shivendra Singh; Alok C. Agrawal (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Bipolar hemiarthroplasty (BHA) is commonly used to treat fracture neck of femur (NOF) in the elderly, despite the fact that the appropriate treatment of fracture NOF is still controversial. In this prospective study, the functional outcomes of NOF fracture after surgery in the elderly, who underwent BHA with a fully coated hydroxyapatite stem with a collar (CORAIL Stem). Materials and Methods: Forty-three consecutive elderly patients with NOF fracture underwent BHA through the lateral Hardinge approach. They were followed up after surgery for 1 year. Two patients expired and one was lost to follow-up and were not included in the study. Postoperative follow-up was done every 4–20 weeks and thereafter at intervals of 3–12 months. Harris hip score (HHS) was recorded at each follow-up visit and complications were noted. Results: Forty patients with a mean age of 77 (62–93) years were followed up after surgery for 1 year. Two patients (4.7%) expired and one (2.3%) was lost to follow-up and were not included in the study. HHS of our cohort of patients averaged 86 (72–99), which falls in the category of a good outcome (80–90). A mild negative correlation (correlation index − 0.2) of age and HHS was observed but was not significant (P = 0.56). Significantly more female patients suffered from NOF fracture (male - 13 [32.5%]: female - 27 [67.5%]; P = 0.03). The left side was injured more often than the right (left 23 [57.5%], right 17 [42.5%]; P = 0.34). Thirty-three patients (83.5%) had one or more comorbid conditions. The mean HHS of female and male patients was 86.41 and 85.39, respectively. This difference was not significant (P = 0.33). There was no difference in outcome, whether an injury occurred to the dominant or nondominant extremity. Complications occurred in seven (17.5%) patients. Conclusions: In the first follow-up year, a good functional outcome with a low complication (17.5%) and mortality rate (4.7%) was observed. Twenty-seven patients (62%) were absolutely pain-free. There were no dislocations, revisions, or additional surgeries in any patients. Most patients returned to their preinjury activity level. To conclude, the procedure is safe and rewarding in the elderly.